Designing a Media Literacy Training Programme for Public Library Staff in Ireland: Preliminary Results and Observations of a University-Public Library Collaboration. Issue 2 (4th March 2023) - Kerrigan, Páraic; McGuinness, Claire; Fulton, Crystal; Siapera, Eugenia; Carrie, David; Pope, Paige
ABSTRACT: While research on media literacy education has focused on varying professional sectors, the role of public libraries in supporting media literacy has yet to be fully explored. This article reports on a university-public library collaboration between University College Dublin, the Libraries Development unit of the Local Government Management Agency (LGMA), the National Adult Literacy Agency (NALA), Meath County Council Libraries and Meta (formerly Facebook). This collaborative partnership sought to develop and pilot a cutting-edge curriculum, incorporating a creative and flexible approach to media literacy training for public library staff. This article details the partnership between the university and the stakeholders toward the common goals of assessing the media literacy training needs of public library staff, and piloting an online professional development course to address these needs. The paper makes several observations on the university-public library collaboration, and proposes that such strategic partnerships might be a key intervention in delivering media literacy education training to the public library sector more broadly.